Determination and prediction of standardized ileal amino acid digestibility of wheat in broilers - X.L. Yun; X.B. Liu; Z.C. Cheng; Y.R. Ji; Y.M. Guo; J.M. Yuan; W. Nie (Poultry Science, 2023)
ABSTRACT: This experiment evaluated the standard ileal digestibility (SID) of amino acids (AA) in 8 different sources of wheat fed to broilers and established prediction equations based on the chemical properties of wheat. A total of five hundred forty 1-day-old broilers were tested in 2 stages (from d 10 to 13 and from d 25 to 28). On d 13, 324 broilers were randomly assigned to 9 diets (6 replicate cages, 6 broilers per cage); on d 28, 216 broilers were randomly assigned to 9 diets (6 replicate cages, 4 broilers per cage). The 9 experimental diets included 8 test diets and 1 nitrogen-free diet. Titanium dioxide was added as an exogenous indicator at 0.5% of the diet. In 8 wheat samples, the mean values of total amino acids (TAA), dispensable amino acids (DAA), and indispensable amino acids (IAA) were 12.16% (CV 13.70%), 7.97% (CV 15.49%), and 4.20% (CV 11.47%). On d 13, the lowest SID of AA was Lys (86.71%), and the highest was Pro (97.98%). On d 28, the lowest SID of AA was His (81.31%), and the highest was Pro (96.83%). There was an effect of wheat source on the SID of AA except for Trp (P < 0.05); the broiler age had an effect on the SID of AA except for Tyr (P < 0.05); the SID of most AA were higher at d 13 compared to d 28. At d 13, the SID of AA was correlated with CP, NDF, and ST (P < 0.05). At d 28, the SID of AA was correlated with EE, Ash, ADF, and NDF (P < 0.05). The R2 value of stepwise regression equations to predict the SID of AA at d 13 was highest for Leu (R2 = 0.972), lowest for Asp (R2 = 0.785); at d 28 was highest for Gly (R2 = 0.995), lowest for His (R2 = 0.678). In conclusion, this experiment showed that the chemical properties of wheat can be used to establish accurate equations for predicting the SID of AA. This made it more efficient to obtain the SID of AA for wheat.